Development of Web-Based Tracer Alumni Information System - Lidya Rosnita; Yesy Afrillia; Rizky Putra Fhonna; Ulva Ilyatin (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2021)
An alumni tracer is a graduate trace study or alumni trail, conducted to students after graduation. Tracer alumni aim to know the outcome of education in the form of transition from the world of college education to the world of work.In writing this practice work report the author conducts an analysis using field studies and literature studies on the alumni data collection system at the Faculty of Social and Political Sciences Malikussaleh University which is still done manually, so that the author decided to build a web-based Tracer Alumni information system that can facilitate the tracking of graduating students, tracer alumni system can also be one of the support for credit the college.This system is designed using PHP/Xampp programming language by using structured diagrams, namely with Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and database design using MySQL.